Pemanfaatan Software Coreldraw untuk Meningkatkan Minat dan Hasil Belajar Matematika Kelas VIII MTS N 6 Karanganyar - Daryono (Jurnal Ilmiah Profesi Guru (JIPG), 2022)
This research purposes to investigate and descript increase interest and mathematic performance of student with functioning software coreldraw. Research type of this research is action research class. Subject research is students of MTs N 6 Karanganyar sum 29 students. Method collecting data is observation, field note, test and documentation. To security validity data uses triangulation technique. Analysis data technique uses method reduction data, serving data and conclusion and verification. Result of the research shows functioning software coreldraw can increases interest and student performance. This increasing shows from: 1) Student’s interesting in learning before action is 34,48% and the last action reach 86,21%, 2) Student’s interesting in paying attention in the materials before action is 27,58% and the last action reach 82,76%, 3) Student’s interesting in uttering the ideas before action is 20.68% and the last action reach 44.83%, 4) repeating the learned materials before action is 17.64% and the last action reach 75.86%, 5) the student performance is fulfillment KKM is 70 before action is 44,83% and the last action reach 86.21%. From the research conclusion functioning software coreldraw can increases interest and mathematic performance of the student.